Trauma to Transformation: the lived experience of bereaved parents of children with chronic life-threatening illnesses in Singapore - Dutta, Oindrila (2020)
In 2016, over 6.6 million children died globally, and 245 children died in Singapore. Chronic illnesses are prevalent causes of child mortality around the world. Despite growing research that examines the lived experience of parents bereaved by their child's chronic life-threatening illness, there is no such study within the Asian context.